THE URGENCE OF THE DEMONSTRATION METHOD IN LEARNING OF FIKH MTS IUJ DDI LERANG-LERANG DISTRICT PINRANG - AHMAD HIBBU HASAN (IAI DDI Polewali Mandar, 2021)
This study discusses the urgency of using demonstration methods in the learning of fiqh material at Madrasah Tsanawiyah IUJ DDI Lerang-lerang, Pinrang Regency, which is the final point to develop student learning achievement. The main problem in the discussion of this research is the urgency of the demonstration method in learning fiqh material, especially regarding the procedures for worshiping Allah Almighty, for example those related to taharah, prayer and the organization of the corpse. The methods used in data collection are observation, distributing questionnaires and interviews. The population in this study were all students at MTs IUJ DDI Lerang-lerang in Pinrang Regency with a sample of 60 people. The sample for Class I is 41 students, the sample for Class II is 42 people, the sample is 21 people, Class III is 36 students, the sample is 18 people, while the jurisprudence educator is only one person so it doesn't need a sample. Sampling using random sampling technique means that each individual has the right to be selected to become a member of the sample. The results of this study indicate that the demonstration method has been applied among educators at MTs IUJ DDI Lerang-lerang in Pinrang Regency in fiqh learning. In order for its application to achieve more optimal results, a combination of methods is used. One method that is often combined is the lecture method. The urgency of implementing the demonstration method in the field of fiqh learning at MTs IUJ DDI Lerang-lerang in Pinrang Regency is that it can increase students' learning motivation, increase student absorption, and can provoke learning initiatives of students. Given the role of the demonstration method in fiqh learning in improving the quality of learning in particular, and the quality of education in general, educators are highly demanded to continue to improve their professionalism in applying these methods.